Rat mRNA expression profiles associated with inhibition of ischemic acute kidney injury by losartan. Issue 4 (9th April 2019) - Wu, Yijin; Peng, Wenying; Wei, Ru; Zhou, Yanhe; Fang, Miaoxian; Liu, Siyi; Deng, Yujun; Yin, Qi; Ouyang, Xin; Hu, Linhui; Hou, Yating; Chen, Chunbo
Abstract : Objective : Losartan was reported to inhibit the progression of acute kidney injury (AKI), but little is known about the underlying pharmacological mechanisms. In the present study, the mRNA expression profiles in ischemic AKI rat kidney altered by losartan treatment were analyzed by next-generation deep sequencing technology. Methods : Ischemia and reperfusion treatment was applied to induce AKI in Sprague–Dawley (SD) rats. The urea and creatinine contents in rat blood were measured. H&E staining was performed to evaluate the histological alteration of rat kidney tissues under a microscope. The TUNEL method was applied to analyze apoptosis in rat kidney tissues. The mRNA profiles in rat kidney were analyzed using next-generation deep sequencing. Differential gene expression was confirmed by quantitative qRT-PCR. Results : The rat model of AKI induced by ischemia and reperfusion showed significant increases in urea and creatinine levels, accompanied by a disrupted kidney tubular structure and renal cell apoptosis. Losartan treatment effectively inhibited the changes in urea and creatinine, tubular structure, and apoptosis in AKI rat kidney. A large number of mRNAs were found to be differentially expressed in the kidneys of AKI rats treated with losartan, which are involved in multiple processes and signaling pathways. The expression of nine differentially expressed genes such as monocyte chemoattractant protein-1 (CCL2) and suppressor of cytokine signaling 3 (SOCS3) was confirmed by qRT-PCR and Western blot. Conclusion : Losartan caused significant alterations in the gene expression profile in AKI rat kidney, which mediated its anti-AKI effects.